2020
DOI: 10.1002/chem.202003246
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Synthesis of Hierarchical Yolk/Double‐Shelled SiOx@TiO2@C Nanospheres for High‐Performance Lithium‐Ion Batteries

Abstract: This work reports the preparation of unique hierarchical yolk/double‐shelled SiOx@TiO2@C nanospheres with different voids by a facile sol‐gel method combined with carbon coating. In the preparation process, SiOx nanosphere is used as a hard template. Etch time of SiOx yolk affects the morphology and electrochemical performance of SiOx@TiO2@C. With the increase in etch time, the yolk/double‐shelled SiOx@TiO2@C with 15 and 30 nm voids and the TiO2@C hollow nanospheres are obtained. The yolk/double‐shelled SiOx@T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 49 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…As a result, the volume change brought on by nano-silicon and Li + alloy/dealloying can be reduced from the inside of the material. Additionally, it works in tandem with the carbon layer to strengthen the stability of the electrode material structure; in addition, the lithium titanate created when Li + and TiO 2 react possesses a fairly large ion diffusion coefficient (2 × 10 −8 cm −2 s −1 ), and that may efficiently speed up the rate at which ions diffuse through the composite, shorten the ion transport radius [55], and deepen the depth of the reaction with Li + . The rate performance of the SiO x , SiO x @C, and SiO x /TiO 2 @C electrode materials is examined in figure 7(c).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the volume change brought on by nano-silicon and Li + alloy/dealloying can be reduced from the inside of the material. Additionally, it works in tandem with the carbon layer to strengthen the stability of the electrode material structure; in addition, the lithium titanate created when Li + and TiO 2 react possesses a fairly large ion diffusion coefficient (2 × 10 −8 cm −2 s −1 ), and that may efficiently speed up the rate at which ions diffuse through the composite, shorten the ion transport radius [55], and deepen the depth of the reaction with Li + . The rate performance of the SiO x , SiO x @C, and SiO x /TiO 2 @C electrode materials is examined in figure 7(c).…”
Section: Resultsmentioning
confidence: 99%
“…After 550 cycles, there is an initial reversible specific capacity of 1093 mA h g −1 at 0.2 A g −1 . Similarly, Gong et al 107 reported a unique SiO x @TiO 2 @C negative electrode material. Tetrabutyl titanate was hydrolysed to coat TiO 2 on the surface of SiO x by the sol–gel method, and phenolic resin was formed on the surface of SiO x by the reaction between resorcinol and formaldehyde, and a carbon shell was formed after calcination.…”
Section: Structural Design Of Siox/c Compositesmentioning
confidence: 87%
“…Resorcinol–formaldehyde (RF) resin is commonly used as a carbon source for preparation of SiO x /C composites due to its low cost and simple synthesis. 44,86–96 Recently, Li's group reported the synthesis of hollow-structured high-capacity SiO x nanocubes (NC@SiO x @m-C) as a LIB anode using a sequential coating strategy in conjunction with a self-sacrificial template method (Fig. 5a).…”
Section: Selection Of the Carbon Source For Siox/c Compositesmentioning
confidence: 99%